2017
DOI: 10.1192/bjp.bp.117.201335
|View full text |Cite
|
Sign up to set email alerts
|

Associations between residual depressive symptoms, cognition, and functioning in patients with euthymic bipolar disorder: results from the FACE-BD cohort

Abstract: International audienceBackgroundThe relationship between residual depressive symptoms, cognition and functioning in patients with euthymic bipolar disorder is a subject of debate.AimsTo assess whether cognition mediates the association between residual depressive symptoms and functioning in patients with bipolar disorder who were euthymic.MethodWe included 241 adults with euthymic bipolar disorder in a multicentre cross-sectional study. We used a battery of tests to assess six cognition domains. A path analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 36 publications
0
24
1
Order By: Relevance
“…Three studies 34,37,38 included samples composed only of BD‐I patients; the other 10 studies reported data on mixed BD samples (composed of type I, type II and/or not otherwise specified). The sample size mostly varied between 12 and 150 individuals, with only one study having a large sample of 241 individuals, 39 thus differing from the others.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies 34,37,38 included samples composed only of BD‐I patients; the other 10 studies reported data on mixed BD samples (composed of type I, type II and/or not otherwise specified). The sample size mostly varied between 12 and 150 individuals, with only one study having a large sample of 241 individuals, 39 thus differing from the others.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 papers included in this review, 12 had or provided enough information to qualify for inclusion in the meta‐analysis stage. In the first step (mean difference), three studies were excluded, 35,39,40 as they lacked data from the control group. In the second step (proportion estimation), 1 study 41 was excluded, as it lacked the proportion of the sample falling below the cut‐off point defined for impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Treating cognitive impairment in people with BD may benefit psychosocial difficulties and improve occupational outcomes . This review evaluated the evidence on cognitive enhancement interventions for people with BD focusing on the different treatment paradigms available and the methodological quality of the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…The association between cognition and function has been extensively explored, with most evidence suggesting significant contributions of cognitive impairment to reduced functional capacities . Cognitive measures have been found to predict psychosocial functioning independently to residual depressive symptoms . Importantly, recent evidence from a large meta‐analysis showed that cognitive performance, particularly verbal memory and executive function, is one of the strongest predictors of favorable employment outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…This overlap and its potential impact on underlying neurobiological mechanism should be taken into account when investigating NS and depression in a transdiagnostic way. Furthermore, it is well known that BD-I patients in the euthymic state as determined by diagnostic criteria and structured interviews, display a broad range of neuropsychological and psychopathological impairments, including sub-syndromal depressive symptoms (Bourne et al , 2013, Roux et al , 2017). These residual depressive symptoms – in contrast to residual hypomanic symptoms – are an important predictor of functional outcome and quality of life (Bonnin et al , 2010, Dias et al , 2008).…”
Section: Discussionmentioning
confidence: 99%